Evaluation of a tax reform: a model with measurement error - Rob Euwals (Institute for the Study of Labor (IZA), 2006)
Parts of the Dutch tax reform 2001 are directed towards fiscal partners in a household and aim at lowering the marginal tax burden of the partner with the lowest (potential) labour income. An important goal of the reform is to increase the employment rate of these partners, which are in majority women. The Dutch Labour Force Survey 1992-2003 shows that the growth of the employment rate of married women after 2001 was larger than for a comparable group of single women. A statistical analysis using a model that accounts for measurement error shows that the growth of the employment rates of women without young children is in line with the predicted effect of the tax reform.
urn:nbn:de:101:1-20090825239
Keywords: 330